(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2024)
Thermal comfort characteristics of polyester and cotton fibres blends (100:0, 50:50 and 0:100) having in four different structures, such as single jersey, cross tuck, cross miss and twill, at two different loop lengths (0.29 cm and 0.32 cm) have been studied. The results evidently prove that the knitted fabrics made from 100% polyester show better thermal comfort properties, possessing an appreciable comfort level; hence they are applicable for active sportswear textiles. The structure and the loop length of the fabric influence the thermal property to a greater extent. The fabric knitted from 100% polyester with a cross-miss structure on a loop length of 0.32 cm shows an excellent thermal comfort characteristic as compared to other samples due to its suitable thermal conduction behavior.